Strategi Komunikasi Pemasaran Bank BTN Kantor Cabang Cikarang dalam Mempromosikan Layanan BTN Prioritas - Utomo, Dendi Riyadi; Yuliantini, Yuliantini (Da'watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study aims to analyze the marketing communication strategy implemented by PT Bank Tabungan Negara (Persero) Tbk Cikarang Branch Office in promoting the BTN Prioritas service. Amidst intense competition in the banking industry within the High Net Worth Individuals (HNWI) segment, Bank BTN faces a strong perception challenge as a housing bank (mortgage) when penetrating the wealth management market. This study employs a qualitative method with a case study approach, where data collection is conducted through in-depth interviews, observation, and documentation studies. The findings indicate that Bank BTN Kantor Cabang Cikarang implements an Integrated Marketing Communication (IMC) strategy to strengthen the Customer Value Proposition "Defining Your Priority". The most dominant promotion mix element is Personal Selling through direct visits, serving as the spearhead to build trust and provide personal financial consultancy. This strategy is synergistically supported by Direct Marketing through the utilization of digital technology (PLUS by BTN Prioritas application, WhatsApp), Sales Promotion through incentive programs, and Marketing Public Relations through the organization of exclusive gathering events. The integration of all these communication elements has proven effective in building BTN's new image and increasing customer engagement in the Cikarang industrial area.